Optimization of 4-Storey Shophouse Construction Project Schedule Using Microsoft Project- Based CPM Method - Betteng, Friska Wanda; Dirgantari, Firza Andhika; Wulandari, Siska; Surahman, Surahman; Suramli, Suramli (Enrichment : Journal of Management, 2025)
Study This aimss to improve efficiency timetable project development building shop house four floor with apply Critical Path Method (CPM) supported by Microsoft Project. The results of the analysis show that time implementation project Can pressed to be 89 days from originally 180 days through identification paths critical and optimization distribution source power. The CPM method is used to identify important activities​ like work foundation, structure building, and completion, while Microsoft Project facilitates appearance and management schedule. Findings from study This driving technology-based project management standardization in the Indonesian construction industry, offering efficient solutions, reducing resource waste and the risk of delays, and strengthening project resilience to market risks